MODEL GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN - Lita Hepika Ginting Lita; Andini Syahputri; Khairun Niswa; Afsha Harnia; Irawan (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2025)
This study analyzes the influence of Good Corporate Governance (GCG) measured through accountability, transparency, and fairness on the Quality of Financial Statements (QFS), wich is assessed based on relevance, reliability, comparability, and understandability. The research method used is quantitative with a causal design. The study population includes individuals who have understanding or involvement in implementing Good Corporate Governance and evaluating financial statement quality, measured through an online questionnaire. The sample consists of 90 respondents who complete the questionnare properly and could be used for analysis. Data were analyzed using PLS-SEM via SmartPLS. The outer model testing shows that all indicators meet the criteria of loading factor > 0.60, AVE > 0.50, and Composite Reliability > 0.70, indicating that all constructs are valid and reliable, the R2 value indicates that Good Corporate Governance has a strong contribution in explaining Quality of Financial Statements. The bootstrapping results reveal that Good Corporate Governance has a positive and significant effect on the quality of fainancial statements, meaning that better implementation of Good Corporate Governance leads to higher-quality financial statements. Overall, this study emphasizes the importance of Good Corporate Governance principles in enhancing transparency, accountability, and the quality of financial information presented by organizations.